Pendidikan Pencak Silat Pagar Nusa dan Relevansinya dengan Tujuan Pendidikan Islam - Lau Han Sein; Ahmad Yusam Thobroni (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2022)
Pagar Nusa's pencak silat education aims to produce pious, worshiping and perfect humans so that they are strong in carrying out life. On the other hand, Islam's attention to education is very large so that the goal of education to make a complete human being (insan kamil) can be realized. This means that the purpose of education in Pagar Nusa pencak silat has a strong relationship with the goal of Islamic education, which cannot be separated from the goal of human creation, in producing superior human beings. This study aims to determine the relevance of Pagar Nusa pencak silat education with the goals of Islamic education. In this research, the writer uses descriptive analytical method, which is looking for verses that have elements of Islamic education goals which are then interpreted. The results of this study indicate that the Pagar Nusa pencak silat activities aim to achieve the values ??of piety and worship to Allah, and make humans perfect caliphs on earth. This is relevant to the goals of Islamic education itself.